How the brazilian football thanks the who drives it and vice versa - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2020)
Football is a blessing. Not so much for those who practice it professionally, but for those who extracted personal, political, and economic promotion from those who promoted their companies and brands, those who obtained control over the workers. Factory football was a hobby. Gradually, other interests sprang up, with entrepreneurs discovering in practice the possibility of obtaining discipline, control over the time of factory workers, curtailing the activities of workers in unions, valuing their products and articles, positive visualization of the company, besides of the image that was concerned with the physical and leisure condition of its workers and search for political promotion. The search for sponsors for the practice also points to a tendency of the Brazilian: to feel protected and to depend on whom he considers superior.
Keywords: Football; Sponsorships; Benefits; Dividends